Milk Yield and Composition and Pasture Ruminal Digestion in Grazing Dairy Cows Receiving Three Levels of Energy Concentrate Supplementation - Salado, Eloy Eduardo (2017)
The objective of the experiment was to determine the effect of feeding three levels (T3.5, T7.0 and T10.5) of energy concentrate (3.5, 7.0 and 10.5 kg cow-1 day-1) on total dry matter (DM) and energy intakes, milk yield and composition, nutritional value of milk and rumen pasture neutral detergent fiber (NDF) digestion in grazing dairy cows. Twenty-one multiparous Holstein cows in early lactation (70.2 ± 13 days postpartum) producing 37.1 (±4.7) kg of milk were assigned to a 3 treatments (7 cows/treatment) × 3 periods Latin square design. Parameters of ruminal environment and pasture NDF degradation were obtained using 3 additional cows of the same breed fitted with rumen cannulae. On a wet basis, concentrate was composed by corn grain (68%), soybean meal (22%), wheat bran (8%) and a vitamin-mineral nucleus with monensin. Pasture (Medicago sativa, sp) was used in a rotational grazing system with an herbage allowance of 30 kg DM cow-1 d-1. Yield (kg cow-1 d-1) of fat corrected milk (4% FCM) resulted higher (p < 0.05) in T7.0 (29.0) compared to T3.5 (26.8) but similar to T10.5 (30.2). Milk and protein yields were linearly increased (p < 0.01) by concentrate intake. Milk fat (3.13 g/100g) and total solid contents (11.79 g/100g) did not differ whereas milk protein (p < 0.03) and casein (p < 0.01) levels (g/100g) increased linearly from 3.05 to 3.10 (protein) and from 2.42 to 2.47 (casein). Pasture intake decreased but total DM and energy consumption were enhanced showing addition effects after concentrate feeding. Body weight (BW) loss and plasmatic levels of non esterified fatty acids (NEFA) decreased with concentrate intake. Circulating levels of insulin-like growth factor-I (IGF-I) were higher (p < 0.05) in T10.5 while those of glucose, plasma urea nitrogen, insulin and somatotrophin were not affected. Ruminal pH and acetate concentration resulted lower (p < 0.05) in T10.5 when compared to T3.5. The acetate:propionate ratio decreased (p < 0.01) from 4.25 in T3.5 to 3.08 in T10.5 and ruminal ammonia nitrogen levels tended (p < 0.07) to be lower as concentrate intake increased. Kinetics parameters of NDF degradation remained unchanged. The potential hypercholesterolemic fatty acids (FA) of milk (C12:0 to C16:0.) remained unchanged as concentrate intake increased. Milk content of linolenic acid decreased and the n-6:n-3 ratio increased with concentrate intake from 1.56 (T3.5) to 2.57 (T10.5) remaining below the recommended values for human health (<4:1). Milk content of antioxidant vitamins was not significantly altered even when pasture DM intake fall in T10.5 compared to T3.5. Increased consumption of a starch-rich concentrate up to 40% of DM intake of cows showed additive effects on total DM and energy intakes improving milk yield, milk protein and casein contents without negative effects on milk fat concentration or yield. Pasture fiber digestion and nutritional parameters linked to healthy value of milk fat were not affected